Psychological Problems and Quality of Life among TransfusionDependent Thalassemic Children: Sharing Experience from a Thalassemia Care Center in West Bengal, India - Nandy Mitra, Mani; Bag, Ranu; Garg, Malini; K. Mandal, Prakas; K. Dolai, Tuphan (International Journal of Nursing Research, 2023)
Introduction: Thalassemia children are highly vulnerable to emotional and behavioral problems. Those born with this congenital deficiency are unable to cope with the illness. Although current treatment strategies aim cure of the disease, a little emphasis is being given at improving the quality of life (QoL) of these patients. Aim: The present study aimed to analyze and explore the common psychological problems and QoL among transfusion-dependent thalassemia children. Materials and Methods: Parents and/or caregivers of 100 children aged between 6 and 12 years with transfusion-dependent thalassemia attending day care services for blood transfusion were interviewed for the assessment of psychological problems using the Childhood Psychopathology Measurement Schedule and QoL was assessed using the EURO-QoL 5 dimension (EQ-5D) tool, an EQ standardized scale. Data were analyzed using standard statistical methods and total scores were expressed as mean, median, and standard deviation. Results: All children had psychological problems with 91% having mild problem and 9% moderate problem; none of the patients had either severe or very severe type of illness. Anxiety and depression (100%), conduct problems (94%), low intelligent quotient and behavioral problems (95%), and somatization (77%) were the main findings. The children were most likely to report impaired QoL due to anxiety and depression (94%), pain/discomfort (91%) followed by difficulty with usual activities (83%), and mobility (67%). Psychological problems were a significant predictor of impaired QOL. Conclusion: Treatment strategies for thalassemia must also aim at recognizing psychological problems and their appropriate and timely management along with emphasis on improvement of QoL.